STUDY OF ANTIMICROBIAL ACTIVITY OF ALCOHOL CHITOSAN FILMS DOPED POLYVINYL TIO2 - León P., Kety (2007)
Poly(vinyl alcohol), PVA, Quitosano-PVA y Quitosano-PVA films doped with TiO2 have been prepared and their antimicrobial properties against S. aureus, E. coli and P aeruginosa have been evaluaied. These films do not have activity to those rnicroorganisms, but they are an effective barrier. These properties make them attractive materials for wound-healing applications and food packaging.